2011
DOI: 10.1103/physreve.84.051129
|View full text |Cite
|
Sign up to set email alerts
|

Interface-roughening phase diagram of the three-dimensional Ising model for all interaction anisotropies from hard-spin mean-field theory

Abstract: The roughening phase diagram of the d=3 Ising model with uniaxially anisotropic interactions is calculated for the entire range of anisotropy, from decoupled planes to the isotropic model to the solid-on-solid model, using hard-spin mean-field theory. The phase diagram contains the line of ordering phase transitions and, at lower temperatures, the line of roughening phase transitions, where the interface between ordered domains roughens. Upon increasing the anisotropy, roughening transition temperatures settle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In our current study, hard-spin mean-field theory [1,2], which has been qualitatively and quantitatively successful in frustrated and unfrustrated, equilibrium and nonequilibrium magnetic ordering problems [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], including recently the interface roughening transition [3], is used to study the roughening of an interface by quenched random pinning center sites or missing bonds. The self-consistency equations of hard-spin mean-field theory [2] are…”
Section: B Method: Hard-spin Mean-field Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…In our current study, hard-spin mean-field theory [1,2], which has been qualitatively and quantitatively successful in frustrated and unfrustrated, equilibrium and nonequilibrium magnetic ordering problems [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], including recently the interface roughening transition [3], is used to study the roughening of an interface by quenched random pinning center sites or missing bonds. The self-consistency equations of hard-spin mean-field theory [2] are…”
Section: B Method: Hard-spin Mean-field Theorymentioning
confidence: 99%
“…This flip will then happen for 2J z = (q − q )J xy , where again q and q are the numbers of xy neighbors bonded to the flipping spin that are, respectively, +1 and −1. The possible values are (q,q ) = (4,0), (3,1), giving the threshold values of J z /J xy = 1,2, calculationally seen in the bottom panels of Figs. 2 and 3.…”
Section: Successive Roughening Thresholdsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is why some MCS, such as the one by Preis, et al [11], demonstrated the use of better hardware, thereby significantly reducing simulation times. Here, we observe solutions that incorporate MFA along one principal direction [7] and hard-spin mean field approximation (HSMFA) [8] compared with the exact solution from KWD.…”
Section: Anisotropy Between 𝑱 and 𝑱′mentioning
confidence: 99%
“…Below the curve is the ordered phase where most of the spins are parallel. As T approaches 𝑇 & , the spins become more randomized eventually reaching the disordered phase where half of the spins points We also compare the behaviour of the curve to the solutions obtained by incorporating MFA along one principal direction [7] and HSMFA [8]. The mean-field theory ignores the interaction between neighbouring edges but instead considers the average behaviour of the spins.…”
Section: Anisotropy Between 𝑱 and 𝑱′mentioning
confidence: 99%